Perspectivas e estratégias para melhoria da educação em engenharia de materiais brasileira - Marcos, Leonardo Pollettini (2020)
Engineering Education (EE) has greatly expanded in Brazil over the last decades and, over the last few years, some criticisms to the Brazilian EE started to gain traction. A reform to the national guidelines for engineering curricula, as well as financial support by CAPES for selected institutional projects targeting the improvement of engineering education were issued as national policies. Naturally, all these aspects extend to Materials Science and Engineering (MSE) education as well. Considering this context, this dissertation focused on identifying the current shortcomings of MSE education in Brazil and at the Federal University of São Carlos (UFSCar), on constructing an overview about the state of EE research around the world and on connecting these shortcomings to the institutions that research them, resulting on a strategic overview of partnerships that would particularly benefit MSE education in Brazil. In order to do so, bibliometrics were employed, and public data from the Questionário do Estudante, UFSCar’s students and internal quality evaluations were investigated. It was verified that the current shortcomings include, among other aspects: the lack of variety on the instructional and assessment methods employed by institutions, the lack of student support, low female representation and a low development of soft skills. On the worldwide research on EE topics, it was verified that the US is the country with the largest scientific output on the field and should be recognized as an international reference, and that there is a wide breadth of topics covered by EE research. Finally, a few institutions were identified for strategic partnerships on a few specific topics, while other institutions presented themselves as strategic for any of the topics related to the shortcomings, due to their great scientific output in the field — notably Purdue University and Virginia Tech, both US-based.